What do outdoor recreationists think of fracking? Politics, ideology, and perceptions of shale gas energy development in Pennsylvania State Forests. (April 2020) - Ferguson, Michael D.; Lynch, Myles L.; Miller, Zachary D.; Ferguson, Lauren A.; Newman, Peter
Abstract: This study examined the influence of political ideology and perceptions of benefits and risks upon State Forest recreationists' support and opposition towards shale natural gas energy development (SGD) on public and private lands in Pennsylvania. Much of the ongoing and proposed Pennsylvania SGD infrastructure is either within or adjacent to public lands, waters, and protected areas, raising concerns about the potential environmental and social impacts upon recreation stakeholders. On-site face-to-face survey interviews were used to gather data from Pennsylvania State Forest recreationists from June to September of 2018 ( n = 392). The predominantly local, educated, experienced, and politically moderate sample in this study demonstrated relatively low levels of support towards SGD on Pennsylvania public lands and relatively neutral stances towards support for SGD on private lands in Pennsylvania. Structural equation modeling results suggested that political ideology and perceptions of risks were significant predictors of support for SGD on both public and private lands in Pennsylvania. The relationship between political ideology and support for SGD on public and private lands was also partially mediated through the perceived risk of SGD in the model. Study findings contributed to previous research suggesting political attitudes may influence and supersede other factors when predicting support for SGD. A series of one-way analyses of variance further explored differences by political ideology in this study. In each of these analyses, a similar statistical trend prevailed. Those identifying themselves as conservative were significantly more likely than their moderate and liberal counterparts to support SGD on both public and private lands in Pennsylvania and perceive fewer risks from SGD on Pennsylvania State Forests. This research lent itself to the theory of landscape fit and construal level theory as State Forest recreationists may have perceived the 'fit' of SGD negatively and could have construed SGD abstractly, lending themselves to political ideology. From a policy and management standpoint, study findings highlight the importance of assessing and communicating State Forest recreationists' perceptions and subsequent opinions when planning, developing, and managing SGD and related decisions in the United States.